Application Of Exact String Matching Algorithms Towards SMILES Representation Of Chemical Structure. - Klaib, Ahmad Fadel; Zainol, Zurinahni; Ahamed Hassain Malim, Nurul Hashimah; Ahmad, Rosma; Hussin, Wahidah (2007)
Bioinformatics and Cheminformatics use computer as disciplines providing tools for acquisition, storage, processing, analysis, integrate data and for the development of potential applications of biological and chemical data. A chemical database is one of the databases that exclusively designed to store chemical information'